Effects of short environmental enrichment in adulthood on neuronal changes in defensive pathway following early-life stress - Ho, Bernice Huiying (2016)
Early-life stress (ELS) have been attributed to psychological issues in the long-term. Maternal separation (MS) is a type of ELS where the offspring is separated from the mother, dysregulating the hypothalamic-pituitary (HPA) axis, a stress regulatory circuit. Behavioral studies suggested that chronic-stress compromises on the defensive pathway. Effects of ELS in the defensive pathway have yet to be clearly elucidated, and this study aims to bridge this gap in understanding. Additionally, this study will determine if short periods of environmental enrichment (EE) in adulthood can rescue the effects of ELS. Neuronal remodeling is affected by stress and stress related hormones, and would be indicative of effects that ELS induces. This study focuses on the ventrolateral (VMHvl) and dorsomedial (VMHdm) part of the ventromedial hypothalamus, and the medial amygdala (MeA), that are essential regions in the defensive pathway. Our results revealed significant morphological effects of ELS in the VMHvl neurons, but not the VMHdm and MeA. EE reduced the effects of ELS in the VMHvl. However, no significant effect of EE was observed in the VMHdm and the MeA. This study hence aims to provide further insights on the effects of MS and EE in adulthood on the defensive pathway.